Journalistic professionalism as performance and boundary work: Source relations at the state house. (January 2014) - Revers, Matthias
In addition to power struggles over representation, negotiations between journalists and news sources represent complex boundary problems. Journalists' efforts at asserting autonomy and offsetting instances when they give it up all provide valuable insights into their understanding of professionalism. The state house, where political actors attempt to influence media representations every day, provides a strategic research site (Merton, 1987) for studying professionalism in source relations. This ethnographic analysis of the Albany press corps looks at professional meanings that are expressed in these negotiations. In interviews conducted for this study, journalists define and distinguish themselves from each other primarily in terms of their understandings of what dealing with source negotiations professionally means. This article introduces the concept of boundary performance to explore how news workers express journalistic professionalism symbolically in action.